1974
DOI: 10.1139/v74-471
|View full text |Cite
|
Sign up to set email alerts
|

Oxydation du cyclohexène par le nitrate cérique d'ammonium

Abstract: The oxidation of cyclohexene by ceric ammonium nitrate has been studied. In anhydrous DMSO the reaction leads to cyclohexene-3-nitrate, while in acetonitrile N-(cyclohexene-2-yl) acetamide is formed. Hydroxylated products are formed in the presence of water. The results obtained are explained in terms of the formation of an intermediate arising from the addition of the radical NO3• to the olefinic double bond. [Journal translation]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Oxidation of cyclohexene by CAN in anhydrous DMSO led to formation of cyclohexene-3-nitrate, whereas in aceto-nitrile, N-(cyclohexene-2-yl) acetamide was formed. 131 Later, Hwu et al reported that alkenes could be nitrated with excess sodium nitrite in the presence of CAN and acetic acid in chloroform. 132 He also showed that the same reagent combination can be used for the ultrasonic nitration of allylsilanes.…”
Section: Introduction Of Nitro Functionalitymentioning
confidence: 99%
“…Oxidation of cyclohexene by CAN in anhydrous DMSO led to formation of cyclohexene-3-nitrate, whereas in aceto-nitrile, N-(cyclohexene-2-yl) acetamide was formed. 131 Later, Hwu et al reported that alkenes could be nitrated with excess sodium nitrite in the presence of CAN and acetic acid in chloroform. 132 He also showed that the same reagent combination can be used for the ultrasonic nitration of allylsilanes.…”
Section: Introduction Of Nitro Functionalitymentioning
confidence: 99%
“…10 Acyclic ketones including those containing nitrate groups are obtained from tertiary cyclic alcohols, 15 from 4 phenylbutan 1 ol, 2 phenyltetrahydrofuran and nitrate of this alcohol. 16 On the oxidation of anthracene, the formation of anthra quinone as a major product with impurities of nitrate 8 and nitrite 9 takes place.…”
mentioning
confidence: 99%
“…In the case of the phosphine oxide (R = Ph), the radical-cation 28 will cyclise to the intermediate 32. Then a well-known ligand exchange with the nitrate from the CAN [30][31][32][33] leads to the new intermediate 33 that will evolve to the desired spirodienone lactam 31 (Scheme 10). We postulate that the phosphine oxide moiety favours the radical cyclisation (path b) instead of the second oxidation to the dication intermediate (path a).…”
Section: Phosphonates Versus Phosphine Oxidesmentioning
confidence: 99%